Characteristics of “Base Genep” Extracts on Treatment Temperature and Extraction Time - Ni Luh Putu Ravi Cakswindryandani; Luh Putu Wrasiati; Lutfi Suhendra (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2020)
“Base Genep” is a Balinese spice that is usually served for all Balinese dishes and is usually served in a wet form. “Base Genep” or “Genep” seasoning must be used until finished because it is made from fresh ingredients that has a short shelf life. “Base Genep” is composed of turmeric, ginger, kencur, galangal, onion, garlic, pepper, coriander, candlenut, nutmeg, chili, shrimp paste, and salt. The content of bioactive compounds derived from the ingredients used makes “base genep” susceptible to oxidation processes that result in decreased quality and shelf life of base genep. This must be prevented by applying technologies such as extraction to increase the weakness of seasonings in the wet form. This study aims to know the effect of temperature and extraction time and determine the best treatment produce “base genep” extract. Extraction process using maceration method with ethanol solvent with temperature treatment and extraction time consisting of a temperature of 30ºC, 40ºC, 50ºC, 60ºC and time for 2, 3, and 4 hours. The results showed that the temperature and extraction time affected the characteristics of “base genep”. The higher the temperature and extraction time until the optimal conditions can increase yield, antioxidant activity, and total phenol extract “genep” seasoning. The results of the research showed a temperature of 50ºC for 4 hours was able to produce the characteristics of the best “genep” seasoning extract with a yield value of 25.392%, IC50 of 280.675 ppm, and a total phenol of 1177.97 mg/100 g.